Theatrical drama and Franciscan simplicity in oratorios by Ferenc Liszt - Subel, Joanna (Interdisciplinary Studies in Musicology, 2018)
The works of Ferenc Liszt are both influenced by the romantic mood and various opposing trends of the church music of his era. In his oratorios Die Legende von der heiligen Elisabeth and Christus, as well as in the unfinished St Stanislaus, one may discern such features as drama, mysticism, universalism, and national elements. In these vocal-instrumental works the composer makes use of two languages, German and Latin, as well as of various types of the archaisms such as quotations from Gregorian melodies. In Liszt’s compositions, choral monodies become ‘motifs’ - the recurring themes which appear frequently and in a variety of versions. Dramatic expression and lyricism are particularly dominant in St Elisabeth. The Christus oratorio, which resembles a misterium, because of the absence of a libretto and the use of liturgical texts, is characterised by the abundance of harmonic solutions. The oratorios reveal both the composer’s uncommon piety and his striving to reform the church music of his times.